Effect of The Addition of Casava Peel and Lactid Acid Bacteria As Feed Additives on The Chemical Profile of Broiler Chicken Meat - Arindya Ayu Perwitarini; Edjeng Suprijatna; Rina Muryani (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2019)
The purpose of this research is to evaluate the effect of feed additives in the form of a combination of cassava peel and BAL on the chemical profile of broiler chicken meat in the form of protein, cholesterol, LDL and HDL broiler chicken meat. The material used was 144 broiler day old chicken (DOC), feed (containing 18.9% protein; 7.3% fat; 7.5% crude fiber; calcium 0.8%; Phosphorus 0.7%; energy metabolic (3044.9 kcal). This research used a completely randomized design with 4 treatments and 6 replications. T0 is a basal ration without the addition of feed additives (control); T1 is a basal ration + 50 ml / kg of feed additive; T2 is a basal ration + 100 ml / kg of feed additives and T3 is a basal ration + 150 ml / kg of feed additives. The results of the analysis of variance showed that the treatment of cassava peel and lactic acid bacteria affected the levels of meat protein and meat cholesterol but did not affect the levels of Low Density Lipoprotein (LDL) and High Density Lipoprotein (HDL) (P <0.05). Meat protein levels T0, T1, T2 and T3 respectively were 18.42%; 18.35%; 18.46% and 17.13%. Cholesterol levels of meat T0, T1, T2 and T3 were 1.49 mg / g; 1.43 mg / g; 1.08 mg / g and 1.05 mg / g. LDL levels of meat T0, T1, T2 and T3 were 0.32 mg / g; 0.35 mg / g; 0.37 mg / g and 0.37 mg / g. HDL levels of meat T0, T1, T2 and T3 were 0.18 mg / g; 0.16 mg / g; 0.15 mg / g and 0.19 mg / g. This study can be concluded that the addition of cassava peel can improve protein levels and reduce cholesterol levels but have not been able to improve LDL and HDL levels of broiler chicken meat.